Tingkat pengetahuan siswa kelas viiiTerhadap kesiapsiagaan bencana gempabumiDi smp n 2 baki kabupaten sukoharjo - SACRISTAN, RISKY (2016)
Sukoharjo regency is one of regencies in Central Java, an area that is prone to earthquake disaster. Earthquake is a physical phenomenon or natural event that is generally characterized by vibrating or berguncangnya earth. The earthquake that occurred in Yogyakarta due to tectonic plate subduction creeping up to the District Tray. This research was conducted in SMP N 2 Baki which aims to determine (1) The level of knowledge of a class VIII student of a catastrophic earthquake (2) The level of preparedness of students of class VIII to the earthquake disaster. The population of this study were all students of class VIII SMP N 2 Baki totaling 660 students. Samples were taken totaling 199 students. The sampling technique used is saturated Sampling. The data collection technique using Guttman scale questionnaire, observation and documentation. Requirements analysis test conducted by validity and reliability testing. The results showed that (1) Knowledge of eighth grade students about the earthquake disaster included enough with a percentage of 47%, as the average respondent answered strongly disagree. (2) The level of preparedness of students of class VIII to the earthquake disaster included in the category is almost ready. It is based on the results of data analysis showed that the percentage of eighth grade level of preparedness against earthquake disaster is 60.30%